Stereotactic Radiosurgery in the Management of Patients With Brain Metastases of Non-Small Cell Lung Cancer: Indications, Decision Tools and Future Directions - Hartgerink, Dianne; van der Heijden, Britt; De Ruysscher, Dirk; Postma, Alida; Ackermans, Linda; Hoeben, Ann; Anten, Monique; Lambin, Philippe; Terhaag, Karin; Jochems, Arthur; Dekker, Andre; Schoenmaekers, Janna; et al. (Frontiers in Oncology, 2018)
Brain metastases (BM) frequently occur in non-small cell lung cancer (NSCLC) patients. Most patients with BM have a limited life expectancy, measured in months. Selected patients may experience a very long progression-free survival, for example patients with a targetable driver mutation. Traditionally, whole brain radiotherapy (WBRT) has been the cornerstone of the treatment, but its indication is a matter of debate. A randomized trial has shown that for patients with a poor prognosis, WBRT does not add quality of life nor survival over the best supportive care. In recent decades stereotactic radiosurgery (SRS) has become an attractive non-invasive treatment for patients with BM. Only the BM is irradiated to an ablative dose, sparing healthy brain tissue. Intra-cranial recurrence rates decrease when WBRT is administered following SRS or resection but does not improve overall survival and comes at the expense of neurocognitive function and quality of life. The downside of SRS compared to WBRT is a risk of radionecrosis and a higher risk of developing new BM during follow-up. Currently SRS is an established treatment for patients with a maximum of four BM. Several promising strategies are currently being investigated to further improve the indication and outcome of SRS for patients with BM: the effectivity and safety of SRS in patients with more than four BM, combining SRS with systemic therapy such as targeted agents or immunotherapy, shared decision making with SRS as a treatment option, and individualized isotoxic dose prescription to mitigate the risk of radionecrosis and further enhance local control probability of SRS. This review discusses the current indications of SRS and future directions of treatment for patients with BM of NSCLC with focus on the value of SRS.